Penentuan Waktu Pemisahan Bibit Kembar Kelapa Sawit (Elaeis guineensis Jacq.) Asal Benih Multi Embrio di Pembibitan - Sukmawan, Yan (Jurnal Penelitian Pertanian Terapan, 2017)
The oil palm (Elaeis guineensis Jacq.) seed generally in form of germinated seed. Germinated seed purchased from oil palm seed producers often contained twin seedlings. The twin seedlings must be separated in pre-nursery before transplanted to the main-nursery. The aim of this research was to determine the best time of oil palm twin seedlings separation in nursery. The research was conducted on April to November 2016 in Politeknik Negeri Lampung. Single-factor experiment was arranged in randomized block design with three replications. The treatment was the age of twin seedling i.e.: 8 weeks after sowing (W1), 9 weeks after sowing (W2), 10 weeks after sowing (W3) and 11 weeks after sowing (W4). The data were analysed by general linear model analysis of variance (ANOVA). The means were separated using HSD at ?=5% level. The result show the best time to separate the twin seedling in pre-nurserys is 9-11 weeks after sowing. Keywords: main-nursery, multi embryo, pre-nursery, twin seedlings